2017
DOI: 10.1016/j.jaci.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of food allergy and other allergic diseases in early childhood in a population-based study: HealthNuts age 4-year follow-up

Abstract: Although the prevalence of food allergy decreased between age 1 year and age 4 years in this population-based cohort, the prevalence of any allergic disease among 4-year-old children in Melbourne, Australia, is remarkably high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
181
4
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(218 citation statements)
references
References 28 publications
7
181
4
10
Order By: Relevance
“…The Australian HealthNuts cohort found an SPT cutoff of 4 mm to have 95% PPV of a positive raw egg white challenge in their population‐based study . Pre‐test probabilities in these populations were however likely to be high as the Italian cohort comprised of infants with known atopic dermatitis and the HealthNuts cohort, albeit a population‐based cohort, had a very high overall prevalence of challenge‐proven egg allergy (11%) . There are currently no studies on skin prick test predictive thresholds for challenge‐proven food allergy in the Asian population, and it is unlikely that thresholds from other populations can be extrapolated to the Asian population.…”
Section: Summary Of Existing Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The Australian HealthNuts cohort found an SPT cutoff of 4 mm to have 95% PPV of a positive raw egg white challenge in their population‐based study . Pre‐test probabilities in these populations were however likely to be high as the Italian cohort comprised of infants with known atopic dermatitis and the HealthNuts cohort, albeit a population‐based cohort, had a very high overall prevalence of challenge‐proven egg allergy (11%) . There are currently no studies on skin prick test predictive thresholds for challenge‐proven food allergy in the Asian population, and it is unlikely that thresholds from other populations can be extrapolated to the Asian population.…”
Section: Summary Of Existing Evidencementioning
confidence: 99%
“…In contrast, egg allergy prevalence is as high as 10% in Australian children below 2 years of age . Peanut allergy predominates in older children with prevalence of up to 3% in the UK, USA and Australia . Apart from Japan, peanut allergy is relatively uncommon in most of Asia …”
Section: Asian Epidemiology On Food Allergy and Timing Of Introductiomentioning
confidence: 99%
“…The prevalence of early childhood food allergy in Australia is among the highest in the world . To reduce the incidence of food allergies, the Australasian Society of Clinical Immunology and Allergy (ASCIA) recently revised their guidelines for infant feeding and allergy prevention, recommending that common food allergens, including peanut and egg, be introduced during the first year of life .…”
mentioning
confidence: 99%
“…; Peters et al . ), has shown that introduction of cooked egg between 4 and 6 months may protect against later egg allergy (Koplin et al . ).…”
Section: Eggs and Complementary Feeding – Changing Advice?mentioning
confidence: 99%